Effect of titanium dioxide blocking layer deposited by cathodic arc plasma on the energy conversion efficiency of dye-sensitized solar cells - S. Sansongsiri (2018)
© 2016 Elsevier B.V. TiO2blocking layers were deposited on commercial fluorine-doped tin oxide (FTO) glasses by cathodic vacuum arc technique for using as working electrodes of dye-sensitized solar cells (DSSCs). These blocking layers were produced between FTO and mesoporous TiO2layers to prevent electron-hole recombination. Photovoltaic performance of the DSSCs with and without TiO2blocking layer by different pulses was investigated. In this research, the film thicknesses with 500–2500 deposition pulses were 47–212 nm. The transmittance was in the range of 60–90% over the visible range with the absorption edge of 356 nm wavelength. The optical energy gaps were determined to be in the range of 3.23–3.34 eV. The deposition of TiO2blocking layer by 1000–2500 pulses was improved the photovoltaic performance. For the 2500 deposition pulses, the DSSC showed the highest energy conversion efficiency of 2.33% or 395% of that without blocking layer. Abstract code: BP22.